DAMPAK LINGKUNGAN TERHADAP KEHIDUPAN MASYARAKAT AKIBAT PERUBAHAN GARIS PANTAI DI PESISIR UTARA PULAU RANGSANG - Aulia Kurniawan; Hadianti, Atrida (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2026)
Small islands in Indonesia are highly vulnerable to shoreline changes caused by human activities, natural factors, and global warming. Rangsang Island experiences annual shoreline changes that have adverse environmental impacts on community livelihoods. This study aims to identify the environmental impacts of shoreline changes on the northern coast of Rangsang Island. A qualitative descriptive method was employed, using word cloud analysis to identify the most dominant impacts experienced by the community based on the frequency and weight of each impact, where larger words or phrases indicate greater intensity and frequency of occurrence. The results reveal several environmental impacts caused by shoreline changes on Rangsang Island, including the loss of plantation and agricultural land, degradation and disappearance of coastal vegetation, land erosion, sea waves inundating inland areas, increased sedimentation, loss of marine resources, seawater intrusion, damage to residential areas, deterioration of environmental infrastructure, collapse of seawalls and wave barriers, soil erosion, and challenges in mangrove reforestation. This study highlights the serious environmental consequences of shoreline changes and provides considerations for mitigation measures to reduce their impacts on small islands in Indonesia, particularly on the northern coast of Rangsang Island.